Menanamkan Nilai Moral Kristiani Kepada Siswa Sekolah Menengah Atas Melalui Implementasi Kurikulum Merdeka dalam Pendidikan Agama Kristen - Lira Tasya; Erika Ratte; Tirsa Tirsa; Nita Toding; Silas Paruru Palabiran (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze how the implementation of the Kurikulum Merdeka supports the cultivation of Christian moral values among senior high school students in Christian Religious Education (PAK) classes. Using a library research method, the study reviews various written sources including books, scholarly articles, and curriculum documents to obtain a comprehensive understanding of how Christian values are integrated into PAK learning. The findings reveal that the Kurikulum Merdeka provides wide opportunities for student-centered, contextual, and character-oriented learning through the Profil Pelajar Pancasila (P5) Project. Christian values such as love, honesty, responsibility, forgiveness, and compassion can be internalized through intracurricular, co-curricular, and experiential project-based activities. The role of teachers as moral exemplars is crucial in guiding students’ character formation. The study also identifies several challenges, including the influence of digital culture, lack of role models within families, and limited instructional time. In conclusion, the implementation of the Kurikulum Merdeka has significant potential to foster Christian character in students, yet requires collaborative support from schools, families, and churches to achieve maksimal outcomes.